2013
DOI: 10.1002/pds.3510
|View full text |Cite
|
Sign up to set email alerts
|

Drug–drug interactions in a cohort of hospitalized elderly patients

Abstract: Hospitalization was associated with an increase in potentially severe DDIs. A significant association was found for mortality at 3 months after discharge in patients with at least two potentially severe DDIs. Careful monitoring for potentially severe DDIs, especially those created at discharge or recently generated, is important to minimize the risk of harm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
43
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 34 publications
8
43
1
3
Order By: Relevance
“…In this study, 62.2 % of the respondents were exposed to at least one potential DDI [including contraindicated (3.6 %), major (32.9 %) and moderate (25.7 %)]. The prevalence of major and moderate DDI in the current study is in line with the findings by Luca et al [31] and Lea et al [32], which reported a prevalence of 63.5, 60.5 % potential DDIs respectively. In contrast to this study, lower prevalence of DDIs was reported from other studies focusing on elderly outpatients [3335].…”
Section: Discussionsupporting
confidence: 93%
“…In this study, 62.2 % of the respondents were exposed to at least one potential DDI [including contraindicated (3.6 %), major (32.9 %) and moderate (25.7 %)]. The prevalence of major and moderate DDI in the current study is in line with the findings by Luca et al [31] and Lea et al [32], which reported a prevalence of 63.5, 60.5 % potential DDIs respectively. In contrast to this study, lower prevalence of DDIs was reported from other studies focusing on elderly outpatients [3335].…”
Section: Discussionsupporting
confidence: 93%
“…A study of more than 2,000 elderly Italian adults at hospital discharge found that almost 70% were exposed to at least one drug-drug interaction and approximately 24% were exposed to a potentially severe interaction. 45 Here, important interactions with four agents or classes (statins, factor Xa inhibitors such as apixaban and rivaroxaban, warfarin, and calcium channel blockers) are briefly reviewed ( Table 2).…”
Section: Important Drug-drug Interactions In Older Adults In Primary mentioning
confidence: 99%
“…One case of death was classified as potentially related to a PIM listed in both versions of Beers' criteria at the 3‐month follow‐up, although associated to a severe DDI. In a recent study conducted on the same cohort of patients and focused on DDIs and related risk of adverse outcomes, we found that five patients were re‐admitted within 3 months after discharge for a severe DDI. In all these cases, patients were not receiving PIMs.…”
Section: Discussionmentioning
confidence: 89%